2010
DOI: 10.1007/978-94-007-0360-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Generation of harmonics and sub-harmonics from an internal tide in a uniformly stratified fluid: numerical and laboratory experiments

Abstract: This paper focuses on the internal tide emitted from a continental slope in a uniformly stratified fluid. Results from numerical simulations using the MITgcm and from laboratory experiments performed on the Coriolis platform in Grenoble are compared. Due to their peculiar dispersion relation, internal gravity waves organize into localized beams of energy. We show that the beam structure is wellpredicted by the viscous theory of [10], assuming that the internal gravity wave field is emitted by a horizontally os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…According to this model, the leading-order (quadratic) nonlinear interactions in the overlap region of the incident and the primary reflected beam drive a mean-flow and a second-harmonic disturbance; the former stays in the vicinity of the slope, while the latter, assuming 2ω is less than the background buoyancy frequency, radiates away along a direction specified by the dispersion relation. These predictions are consistent with laboratory experiments [15,16] as well as numerical simulations [17,18].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to this model, the leading-order (quadratic) nonlinear interactions in the overlap region of the incident and the primary reflected beam drive a mean-flow and a second-harmonic disturbance; the former stays in the vicinity of the slope, while the latter, assuming 2ω is less than the background buoyancy frequency, radiates away along a direction specified by the dispersion relation. These predictions are consistent with laboratory experiments [15,16] as well as numerical simulations [17,18].…”
Section: Introductionsupporting
confidence: 89%
“…Here ρ has been rescaled to account for the resonant behavior of ρ = O(ε/δ) = O(ε 1/3 ) in the near-critical range δ = O(ε 2/3 ) defined in Eq. (17). Substituting these expansions in Eqs.…”
Section: Near-critical Beam Reflectionmentioning
confidence: 99%
“…It is, however, worth noting that we systematically observe low values of b/a over the Reykjanes Ridge. This bias toward higher frequency possibly suggests that high-frequency waves are generated by interactions between the tide and the topography of the Reykjanes Ridge (Gerkema et al 2006;Gerkema 2006;Pairaud et al 2010). Low values of b/a are also found in the Iberian basin at and below the depth of the Mediterranean outflow water, between 1000 and 1800 m. For an environment located below the Mediterranean outflow water, at a depth of 1400-1500 m in the Canary basin, van Haren and Gostiaux (2009) …”
Section: A Mean Dissipation Rate and Observed Variability Rangementioning
confidence: 98%
“…Clark & Sutherland (2010) indirectly linked this breakdown to PSI, a hypothesis also supported by numerical simulations. Furthermore, PSI was noted in an experimental-numerical study of a model internal tide (Pairaud et al 2010), as well as in numerical simulations of the reflection of a localized nearly monochromatic wave beam from a horizontal surface (Zhou & Diamessis 2013). Finally, recent experiments (Bourget et al 2013) have revealed that resonant triad interactions can bring about instability in a localized wave beam that comprises just three wavelengths of a sinusoidal wavetrain.…”
Section: Introductionmentioning
confidence: 94%